Utilization of Seagrass Leaf Waste (Thalassia hemprichii) as Feed Ingredient for Koi Fish (Cyprinus rubrofuscus) Growth: English - Anita Prihatini Ilyas; Muh Fahruddin; Astutiwati; Wiwin Apri Hartina (Journal of Aquaculture and Fish Health, 2026)
Several alternative feed ingredients can be used in feed production, one of which is the addition of seagrass leaf waste flour in feed formulations. This study aims to determine the use of seagrass leaf waste as a feed ingredient on the growth of koi fish (Cyprinus rubrofuscus). This study was conducted for 30 days at Bhayangkara Residence Baiti Jannati Block T No. 3, Samapuin Village, Sumbawa Regency. This study used an experimental method with a completely randomized design (RAL) consisting of 4 treatments of different doses of seagrass leaf waste flour mixed with other feed raw materials in the form of pellets. The results showed that the highest absolute weight gain was found in treatment P1 with a weight of 20 g, followed by treatment P2 with 5% seagrass leaf waste flour added to the pellet feed at 18 g, treatment P3 at 14 g, and the lowest in treatment P4 at 9 g. Meanwhile, the highest survival rate in this study was shown by treatment P2 at 100%, followed by treatment P3 at 97%, and the lowest was in treatments P1 and P4, which were 90% each.